2002
DOI: 10.2527/2002.80123257x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding a blend of grains naturally contaminated with Fusarium mycotoxins on swine performance, brain regional neurochemistry, and serum chemistry and the efficacy of a polymeric glucomannan mycotoxin adsorbent1

Abstract: The co-occurrence of Fusarium mycotoxins in contaminated swine diets has been shown to result in synergistic toxicity beyond that observed for individual toxins. An experiment was conducted, therefore, to investigate the effects of feeding a blend of grains naturally contaminated with Fusarium mycotoxins on growth, brain regional neurochemistry, serum immunoglobulin (Ig) concentrations, serum chemistry, hematology, and organ weights of starter pigs. Three levels of glucomannan polymer (GM polymer, extract of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
115
8
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 38 publications
16
115
8
3
Order By: Relevance
“…Contrary to Edrington et al (1994) in growing lambs, we did not observe a specific effect from aflatoxin on Hct and WBC, probably because of our lower mycotoxin concentration. Our results on RBC features differed from those by Swamy et al (2002) probably because of the differences in the Fusarium mycotoxins blend (in that case, based on DON and fusaric acid).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to Edrington et al (1994) in growing lambs, we did not observe a specific effect from aflatoxin on Hct and WBC, probably because of our lower mycotoxin concentration. Our results on RBC features differed from those by Swamy et al (2002) probably because of the differences in the Fusarium mycotoxins blend (in that case, based on DON and fusaric acid).…”
Section: Discussioncontrasting
confidence: 99%
“…The increased plasma Cl Figure 3 Puberty attainment of dairy heifer in the three experimental groups during the monitored period for puberty assessment. level in A-F heifers agrees with the observation described by Swamy et al (2002) in swine fed grains naturally contaminated with Fusarium mycotoxins (mainly DON and fusaric acid). The same increase in plasma Cl was observed in rats (Takahashi et al, 2008), as a sign of subchronic toxicity from a nivalenol contamination.…”
Section: Discussionsupporting
confidence: 90%
“…Rotter et al (1994) observed an increase in the percentages of segmented neutrophils and the remaining leukocytes in pigs fed diets contaminated with DON at 0.75-3 mg/kg of feed for 28 days. Swamy et al (2002) noted a decrease in plasma Ca, P in . and Cl concentrations in piglets fed a diet contaminated with DON at 5.5 mg/kg of feed for 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the negative effects of DON on growth performance, anti-mycotoxin additives can be added to the diet. However, most commercial anti-mycotoxin additives (e.g., glucomannans, aluminosilicate) are not effective, the capacity of these additives to mitigate the effects of Fusarium mycotoxins on growth performance being limited (Da¨nicke et al 2004a(Da¨nicke et al , 2007Do¨ll et al 2005), or did not give consistent results (Swamy et al 2002(Swamy et al , 2003Diaz-Llano and Smith 2006), the exception being PV Patience et al 2014;Le Thanh et al 2015).…”
mentioning
confidence: 99%
“…The blend of yeast cells, bacteria and plant extracts would be efficient to mitigate the negative effect of Fusarium toxins on growth performance in poultry (Da¨nicke et al 2002;Ghareeb et al 2012) but not in pigs (Barnes et al 2010), whereas aluminosilicates were not able to mitigate adverse effects of trichothecenes in pigs (Do¨ll et al 2005). The capacity of organic ligands, such as glucomanans, to reduce the effects of Fusarium toxins on growth performances is limited and has provided conflicting results (Swamy et al 2002(Swamy et al , 2003Diaz-Llano and Smith 2006). The anti-mycotoxin additive, containing a blend of vitamins, antioxidants and preservatives (ascorbic acid, citric acid, potassium sorbate and sodium metabisulfite), has been shown to restore growth performance in pigs fed a diet contaminated with DON (Patience et al 2014).…”
mentioning
confidence: 99%